2016
DOI: 10.1016/j.exppara.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro characterization of Leishmania (Viannia) braziliensis isolates from patients with different responses to Glucantime® treatment from Northwest Paraná, Brazil

Abstract: Leishmaniasis is a group of diseases that presents various clinical manifestations. Many studies have shown that the parasite plays an important role in the clinical manifestations and prognosis of this disease. The cutaneous and mucosal forms of American tegumentary leishmaniasis (ATL) are associated with Leishmania (Viannia) braziliensis, which exhibits intraspecific genetic polymorphisms and various clinical manifestations. The present study focused on four different L. braziliensis strains that were isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…[26] identified two different genotypes of L. braziliensis (Ab1 and Ab2), and one of them (Ab2) was only found in the zone of the Zenta valley (Yungas Ecoregion), which is where we found most cases of TF. Studies from Brazil reported intraspecific differences (eg genetic, ultrastructural) in isolates from patients with different responses to treatment [27,28].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…[26] identified two different genotypes of L. braziliensis (Ab1 and Ab2), and one of them (Ab2) was only found in the zone of the Zenta valley (Yungas Ecoregion), which is where we found most cases of TF. Studies from Brazil reported intraspecific differences (eg genetic, ultrastructural) in isolates from patients with different responses to treatment [27,28].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…This includes decreasing NO production (Vodovotz et al, 1993;Bogdan, 2020), which is one of the principal defense mechanisms against infection (Bogdan, 2020). In vitro studies using the same strains as our study have not detected NO production by macrophages (Fernandes et al, 2016).…”
Section: Discussionmentioning
confidence: 45%
“…For example, in BALB/c and C57BL/6 mice, different profiles of inflammatory infiltrates in livers and spleens were found with or without the presence of parasite (Pereira et al, 2009). Fernandes et al (2016) demonstrated various cytokine expressions and macrophageinfectivity rates in in vitro experiments with the same strains used in our study.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations